THE EFFECT OF PERIODONTAL PACK WITH ADDITIONAL PLANTS OF IODINE (JATROPHA MULTIFIDA L.) POST CURRETAGE - Ade Ismail Abdul Kodir; Muhamat Muhtar S Abdurrohman; Talitha Novi Rahmaningrum (Jurnal Medali, 2022)
Background: Curettage is an act of scraping the granulation tissue on the lateral gingival wall of the periodontal pocket. After curettage, a periodontal pack was applied to control bleeding and keep the wound area clean. The addition of iodine leaves as an alternative because it contains flavonoids that can help the wound healing process. This study aims to determine the effect of adding 10% iodine leaf extract gel on the curettage process.Method: A true experimental laboratory study with a post-test only control group design on 20 wistar rats. The periodontal pack group and the periodontal pack group were added with 10% iodine leaf extract gel. Curettage healing was seen from the mean number of fibroblasts using One-Way Anova analysis.Result: The study showed the mean number of fibroblasts on the 5th and 7th day periodontal pack groups were 35.20 and 49.60, while those in the periodontal pack group with the addition of iodine leaf extract gel on 5th and 7th days were 45.80 and 50.80, respectively. The One-Way Anova test showed p > 0.05, there was a significant difference in the mean number of fibroblasts between the study groups.Conclusion: The conclusion is that there is an effect of giving 10% iodine leaf extract gel on the number of fibroblasts in the healing process of wistar rat curettage.